Produção de álcool combustível em pequena escala: desenvolvimento da tecnologia de destilação apropriada - Mayer, Flávio Dias (2010)
The small scale fuel ethanol production faces serious problems of inefficiency inherent to the process. The yield increase in distillation step presents a promising way to guarantee technical and economical feasibility to microdistilleries. As the general objective, it is proposed a different still, a hybrid miscellaneous of plates and packing, in stripping and rectifying sections respectively, and as a specific objective, to explore the best technical features of each tower internals. The studied prototype consists of one glass constructed continuous operation bench still, divided in 3 modules of 190cm effective height and a 4cm internal diameter; two modules filled with Raschig rings and one module as vigreux type. Tests were performed under total reflux, and later in continuous operation. In total reflux, the number of transfer units and the height of transfer unit were determined, referred to liquid and gas phases. The obtained values were approximately and respectively: 11,6 and 10,3; and 0,1847cm and 0,1632cm. The theoretical stages number was determined using four different methods that allowed evaluate the height equivalent to a theoretical plate. Standing out is the method proposed by Katayama, whose values were closer to the number and height transfer unit, 9,18 and 0,1733m respectively. Subsequently, seven experiments were performed (A, B, C, D, E, F and G) in continuous operation, differ only on their variable rate of vaporization, in order to assess their influence in the still operating performance (minimal distillated ethanol concentration - 83,04% mol, and maximum bottom ethanol concentration 0,196% mol, operational capacity and energetic factor). Therefore experiment C showed the lowest reflux ratio (2,293)and the highest energy factor (1,342), besides complying the concentration limits for the distillate (83,14% mol) and bottom product (0,16% mol). By comparing the experiments of higher (A 84,24% mol) and lower (E 82,82% mol) distillate concentration was concluded that, in order to obtain a small gain in distillate concentration (1,71%), it was necessary an increase of 226,07% in the A reflux ratio compared to E experiment, resulting in an increase of 51,38% in specific energy consumption. Thereby the A energetic factor experiment was approximately 50% smaller. It can be stated that these results prove the technical feasibility of proposed miscellaneous still, with wide application in microdistillaries.